OVERCOMING BARRIERS TO DIGITAL FINANCIAL INCLUSION: A CASE STUDY OF MICRO ENTERPRISES IN TOMOHON: Mengatasi Hambatan dalam Inklusi Keuangan Digital: Studi Kasus Usaha Mikro di Tomohon - Priskila Gissela Marlia Walangitan (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This research investigates the impact of digital financial inclusion on the marketing strategies of micro enterprises in Tomohon, Indonesia. Digital financial inclusion refers to the accessibility and use of financial technology by micro enterprises to enhance their operations and marketing efforts. The study employs a qualitative approach, utilizing in-depth interviews and case studies to gather data from micro enterprise owners who have adopted digital financial technology. The findings reveal that while the adoption of digital financial technology among micro enterprises in Tomohon is still limited, it has shown significant potential in improving marketing efficiency and expanding market reach. The use of social media platforms, e-commerce, and digital payments has enabled these enterprises to overcome geographical limitations and reach a broader customer base. However, the research identifies several challenges, including low financial literacy, inadequate technological infrastructure, and limited support from government and financial institutions. These challenges hinder the widespread adoption of digital financial technology among micro enterprises. To address these issues, the study recommends the development of comprehensive financial literacy programs, investment in technological infrastructure, and incentives for the adoption of digital payments. Continuous monitoring and evaluation of these initiatives are essential to ensure their effectiveness in promoting sustainable growth and inclusivity. The research concludes that digital financial inclusion can be a catalyst for economic growth and development in Tomohon, provided that the identified barriers are effectively addressed.